Effect of sodic water, biofertilizer and phosphorus on physical properties of soil, yield attributes and yield of mungbean - Kumari, Subhita; Yadav, B.L.; Verma, H.P.; Meena, J.S.; Pancholi, Pinky (Annals of Agricultural Research, 2016)
A pot experiment was conducted to asses the effect of phosphorus management and biofertilizer in mungbean irrigated with sodic water during 2013. Three levels each of sodic water (control, 3.0 and 6.0 mmol/L), biofertilizer (control, PSB and PSB + VAM) and phosphorus (control, 15 and 30 mg/ kg of soil), were tested in factorial randomized block design with three replications. The results indicated that application of irrigation water having RSC 1.0 mmol/L, biofertilizer viz. PSB + VAM and phosphorus 30 mg/kg of soil recorded the maximum and significantly higher total and available phosphorus, dehydrogenase enzyme activity, alkaline phosphate activity, total and effective nodules, nodule index, number of pods per plant, grain yield, straw yield and biological yield of mungbean over rest of the treatments. A application of irrigation water having RSC 6.0 mmol/L recorded significantly higher pH, EC and ESP as compared to other treatments. However, pH, EC and ESP did not show any significantly difference under different levels of phosphorus and biofertilizers.